THE EFFECT OF PICURE STORY VIDEO MEDIA ON THE SPEAKING SKILLS IMPROVEMENT OF CHILDREN WITH INTELLECTUAL CHALLENGES AT GRADE IV SPECIAL EDUCATION SCHOOL CLASS C (SPLB-C) OF CIPAGANTI SPECIAL EDUCATION FOUNDATION (YPLB CIPAGANTI) - Sutisna, Nia (EDUTECH, 2015)
Abstract. Children with intellectual challenges are those who experience barriers to intelligence, such as low academic skills, low personal and vocational abilities and have impaired speech. Further, those children have to deal with fine motor skills and hand-eye coordination which are essentially needed in speaking and performing various daily activities such as writing. The problem that is often faced by children with intellectual challenges is difficulty in beginning writing at the stage of imitating or copying text. Another problem found in children with intellectual challenges is related to communication barrier or developing oral language skills in accordance with society norms so that they are able to catch the feeling and the idea of the people they speak to and play active role in the society. To achieve the goals, there needs to be sufficient speaking practice or speech education using picture story video media with supporting activities. Therefore, this research aimed to find out the effect of using picture story video media in improving the speaking skills of children with intellectual challenges. This research used experimental method with One Group Pre Post Test design and Wilcoxon test. The subjects are four children with intellectual challenges at Grade IV SPLB-C YPLB Cipaganti.Keywords: video media, children with intellectual challenges, speaking skillsAbstrak. Anak tunagrahita adalah mereka yang mengalami hambatan dalam inteligensi, seperti rendahnya kemampuan akademik, kemampuan personal, kemampuan vokasional, dan mengalami gangguan berbicara. Selain itu, anak tunagrahita ringan mengalami motorik halus dan koordinasi mata tangan sangat diperlukan untuk berbicara dan melakukan berbagai aktivitas yang terkait dengan kehidupan sehari-hari seperti untuk menulis. Adapun masalah yang sering dihadapi anak tunagrahita dalam kemampuan menulis permulaan yaitu pada tahapan meniru atau menyalin tulisan.Masalah yang ditemukan pada anak tunagrahita yaitu berkaitan dengan hambatan berkomunikasi atau mengembangkan kemampuan bahasa lisan/berbicara sesuai dengan norma lingkungan dan dapat menangkap perasan dan gagasan lawan bicara serta berperan aktif dalam lingkungan. Untuk merealisasikan usaha tersebut perlu adanya latihan berbicara atau speech education yaitu melalui media video cerita yang memadai dan bentuk kegiatan yang menunjang. berdasarkan latar belakang masalah tersebut timbullah sebuah rumusan masalah dalam penelitian ini, yaitu: â€œAdakah pengaruh penggunaan media cerita bergambar terhadap peningkatan kemampuan berbicara Anak Tunagrahita Ringan?â€ Dalam menjawab permasalahan penelitian tersebut, peneliti menggunakan metode eksperimen dengan bentuk One Group Pre test Post test Design uji Wilcoxon. Adapun subjek dalam penelitian ini adalah empat orang siswa tunagrahita kelas IV SPLB-C YPLB CipagantiKata kunci: media video, tunagrahita, kemampuan berbicara